Roles of the Dbl family of RhoGEFs in mechanotransduction – a review - Ohashi, Kazumasa; Kunitomi, Aoi; Chiba, Shuhei; Mizuno, Kensaku (Frontiers in Cell and Developmental Biology, 2024)
Rho guanine nucleotide exchange factors (RhoGEFs) comprise a wide range of proteins with a common domain responsible for the activation of the Rho family of small GTPases and various domains in other regions. The evolutionary divergence of RhoGEFs enables actin cytoskeletal reorganization, leading to complex cellular responses in higher organisms. In this review, we address the involvement of RhoGEFs in the mechanical stress response of mammalian cells. The cellular mechanical stress response is essential for the proper and orderly regulation of cell populations, including the maintenance of homeostasis, tissue morphogenesis, and adaptation to the mechanical environment. In particular, this review focuses on the recent findings regarding the Dbl family of RhoGEFs involved in mechanical stress responses at the cell-cell and cell-substrate adhesion sites, and their molecular mechanisms underlying actin cytoskeleton remodeling and signal transduction.